2019
DOI: 10.1016/j.apcatb.2018.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensionally ordered macroporous PrOx: An improved alternative to ceria catalysts for soot combustion

Abstract: which significantly enhances the solid-solid soot-catalyst contact. This enhanced contact, together with the improved reducibility of PrOx regarding CeO2, ameliorate the active oxygen production and its transfer to soot particles, improving the soot combustion with O2. In addition, the higher ability of PrOx to oxidize NO to NO2, improves the soot combustion in a higher extent than CeO2 in presence of NOx. The catalytic activity of PrOx-3DOM after several soot combustion cycles is also confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…As it was found by XPS, the surface of 3DOM Ce-Pr-O x catalyst can be more easily reduced and re-oxidized than that of the reference material prepared without template, mainly due to the presence of praseodymium cations rather than cerium ones [ 85 ]. By the way, PrO x with 3DOM structure is even more active in PROX than corresponding CeO x due to better reducibility [ 86 ].…”
Section: Ceria Preparation Methods Based On Artificial Templatesmentioning
confidence: 99%
“…As it was found by XPS, the surface of 3DOM Ce-Pr-O x catalyst can be more easily reduced and re-oxidized than that of the reference material prepared without template, mainly due to the presence of praseodymium cations rather than cerium ones [ 85 ]. By the way, PrO x with 3DOM structure is even more active in PROX than corresponding CeO x due to better reducibility [ 86 ].…”
Section: Ceria Preparation Methods Based On Artificial Templatesmentioning
confidence: 99%
“…However, the contribution of ceria cannot be ruled out because of its well-known moderate basicity. 43–45…”
Section: Resultsmentioning
confidence: 99%
“…Among the above morphologies, due to the interconnected macroporous structure with large pore diameter (>50 nm) and low diffusion resistance, the 3DOM catalyst has enough migration space for soot particles in its internal pores, which are expected to show excellent catalytic ability [15][16][17]. Many previous studies have shown that the catalytic performance of 3DOM oxide-based catalysts for soot combustion is superior to that of corresponding nanoparticle catalysts due to their structural effects [18][19][20]. To improve the intrinsic activity, a series of 3DOM oxides-supported Au and Pt catalysts have also been prepared in our research group, and the prepared 3DOM oxides-supported noble metal catalysts exhibit excellent catalytic ability in soot combustion reaction [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, considering the economy of catalyst cost, a number of rare earth oxides and transition metals have been studied for soot combustion [20,[24][25][26]. MnO x -CeO 2 mixed oxides with Mn and Ce synergistic effects have become one of the low cost and high performance catalysts [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%